Malignant neoplasms originating from the bones of the foot: Predilection of hematological malignancies and sex‐related and ethnic disparities in amputation. Issue 8 (5th August 2021) - Jawad, Muhammad Umar; Farhan, Saif B.; Haffner, Max R.; Kreulen, Christopher D.; Giza, Eric; Thorpe, Steven W.; Randall, R. Lor
Abstract: Purpose: Neoplasms originating from the "small bones of the lower limb and the overlapping joints" are rare but portend a serious prognosis. Current study utilizes a population‐based registry in the United States to characterize the malignancies of the foot. Methods: National Cancer Institute's Surveillance, Epidemiology and End Result database from 1975 to 2017 was queried to report incidence and survival data in 514 patients in the Uited States. Kaplan–Meier and Cox Regression were used to determine the prognostic factors affecting survival. Chi square test was used to assess the correlation. Results: Hematological malignancies constituted 14.8% of the entire cohort. Incidence of the foot neoplasms was 0.024 per 100 000 persons in 2017 and has not significantly changed since 1975 ( p > 0.05). Disease‐specific‐5‐year survival for the entire cohort was 73%. On multivariate analysis younger age groups, "localized" stage and extent of surgical resection were predictors of improved outcomes. A significant correlation was found between amputation with male sex and Hispanic ethnicity. Conclusions: The current study analyzes data from population‐based registry reporting incidence and survival data for patients with neoplasms of the foot. Independent prognostic factors include age, stage and extent of surgical resection. Amputation was found to be associated with male sex and Hispanic ethnicity.